PENGARUH INVESTASI ASING DAN INVESTASI DALAM NEGERI TERHADAP TINGKAT PENGANGGURAN DI PROVINSI SUMATERA SELATAN - Zulkifli Djamin (Majalah Ilmiah Manajemen STIE Aprin Palembang, 2020)
Investment is an investment activity that makes the economy grow. Mainly through the opening of new jobs. Investment can come from abroad and within the country. This study analyzes the effect of foreign investment and domestic investment on the unemployment rate in South Sumatra. The study uses multiple linear regression analysis techniques. Unemployment is the dependent variable, while foreign investment and domestic investment are independent variables. Based on the research results of the domestic investment variable (INVESDN) significantly influence the unemployment rate (UNEMP) in South Sumatra. While the investment variable of foreign investment (FDI does not significantly influence the unemployment rate because t-count is smaller than t-table.